2012
DOI: 10.1002/anie.201205027
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Metal–Metal Quintuple Bonds with Alkynes: [2+2+2] and [2+2] Cycloadditions

Abstract: High five! The quintuply bonded molybdenum amidinate 1 reacts with two equivalents of 1‐pentyne through a [2+2+2] cycloaddition reaction to give the first examples of the benzannulated product 2. The C4Mo2 rings exhibit aromatic character. Treatment of 1 with internal alkynes afforded the 2:1 and 1:1 [2+2] cycloadducts, which are mechanistically associated with the formation of 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…The transition‐metal‐catalyzed cyclotrimerization of acetylenes to benzene derivatives, first reported in 1948 by Reppe et al ., is a groundbreaking example of a metal‐mediated [2 + 2 + 2] cycloaddition reaction. [ 14 ] Since then, diverse transition‐metal catalysts have been developed successively for the synthesis of benzene derivatives, such as half‐sandwich CpM‐based (Cp = ƞ 5 ‐cyclopentadienyl, M = Co, Rh, Ir) complexes [ 15–17 ] and homonuclear complexes containing metal–metal multiple bond, [ 18 ] which accelerated the application of metal catalysts in this field. By now, there are many theoretical and experimental studies on the formation of benzene from acetylene cyclotrimerization, which mainly involve the reactivity of mononuclear/homobimetallic metal complex.…”
Section: Introductionmentioning
confidence: 99%
“…The transition‐metal‐catalyzed cyclotrimerization of acetylenes to benzene derivatives, first reported in 1948 by Reppe et al ., is a groundbreaking example of a metal‐mediated [2 + 2 + 2] cycloaddition reaction. [ 14 ] Since then, diverse transition‐metal catalysts have been developed successively for the synthesis of benzene derivatives, such as half‐sandwich CpM‐based (Cp = ƞ 5 ‐cyclopentadienyl, M = Co, Rh, Ir) complexes [ 15–17 ] and homonuclear complexes containing metal–metal multiple bond, [ 18 ] which accelerated the application of metal catalysts in this field. By now, there are many theoretical and experimental studies on the formation of benzene from acetylene cyclotrimerization, which mainly involve the reactivity of mononuclear/homobimetallic metal complex.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting parallel structural feature of 5 and 6 with [(Et 3 P) 2 Pt(π‐alkyne)] is that both amidinate ligands also bend back away from the Pd and Pt centers by about 11.8° and 12.8°, respectively, much smaller than that of the 3‐hexyne‐coordinated 2 (ca. 25°), which features a formal MoMo quadruple bond 13d. The PdMo bond lengths, 2.7200(11) and 2.7168(10) Å in 5 are longer than two crystallographically identical PtMo bond of 2.6750(5) Å in 6 .…”
Section: Methodsmentioning
confidence: 95%
“…Preliminary reactivity examinations on these low‐coordinate dinuclear species revealed that the presence of δ‐bond charge density enable them to react with small inorganic molecules11 and organic functionalities 11. 12 For example, these species underwent reductive complexation with the pnictogen elements13a and unsaturated hydrocarbons 13bd. Of particular interest is that, like unsaturated hydrocarbons, they underwent electrophilic addition reactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] In this review,w ef ocuso nt he syntheses, structures, and reaction chemistry of metallacyclobutadienes. Although interesting, the chemistry of closely relateds pecies such as deprotio metallacyclobutadienes, [6] dimetallacyclobutadienes, [7] andh eterometallacyclobutadienes (e.g.,a zametallacyclobutadienes [8] ) are not included. For easy presentation,t he C 3 R 3 ligand in a metallacyclobutadiene [M(C 3 R 3 )L n ]i sv iewed as at rianionic [C 3 R 3 ] 3À ligand,a nd metallacyclobutadienes are classified as either high-valent (Schrock) or low-valent (Fischer) types in the following discussions.…”
Section: Introductionmentioning
confidence: 99%